Achalasia-like Motility Disorder in a Kidney Transplant Recipient - Bender, Sascha T; Obst, Wilfried; Mertens, Peter R; Gross, Christian (Archives of Clinical and Biomedical Research, 2021)
We present a case of tacrolimus intoxication with an achalasia-like esophageal motility disorder in a long term-term renal recipient, who was admitted to hospital because of an acute on chronic kidney transplant injury and newly onset dysphagia. Esophageal manometry secured the diagnosis. Unfortunately despite recovered kidney function the clinical outcome of our index patient was fatal. He deceased in consequence of an extensive esophageal rupture. Our case demonstrates a rare but potentially serious complication of post-transplant patients on calcineurin inhibitors. Calcineurin inhibitor-induced achalasia should be considered in this population when newly onset dysphagia occurs with otherwise negative workup.